Endoplasmic reticulum stress in lung cancer - Zhang, Donghuan; Lin, Lanlan; Jin, Hui; Mao, Huajun; Wang, Luying; Ma, Wenwen; Lao, Zhenghong (Frontiers in Oncology, 2025)
Endoplasmic reticulum is the primary site of eukaryotic cells involved in biosynthesis, lipid metabolism, glucose metabolism, protein folding and secretion. Multiple factors in the tumor microenvironment may induce the accumulation of unfolded and misfolded proteins in the endoplasmic reticulum and trigger endoplasmic reticulum (ER) stress. Adaptive mechanisms including unfolded protein response (UPR) and endoplasmic reticulum associated degradation (ERAD) are activated in response to ER stress. Previous studies have revealed that ER stress may participate in epithelial mesenchymal transformation, apoptosis, metabolic regulation and drug resistance of lung cancer cells. Herein, we summarized the potential effects and regulatory mechanisms of ER stress on the biological process of lung cancer, which may provide scientific significance and clinical value for elucidating the adaptability of lung cancer cells under stress and developing novel targeted therapies.